Nature and human health - Kirsanova, Santa (2021)
Outdoor environment is one of the most important factors in a person‘s physical, mental and emotional development. This thesis concerns the opportunities within landscape architecture to promote the development of the outdoors as a resource for health and well-being in healthcare settings. The overall aim is to describe the main principles of providing a restorative outdoor environment around healthcare settings. Natural environments (Natural elements in outdoor environments) meet these criteria for a successful restorative environment. As such, benefits of integrating natural elements within healthcare settings to improve user experience and promote patient well-being. This is a theoretical review based on literature studies including research done by professionals in various fields, and interviews with persons, who have done research in these specific fieldsrestorative environments around healthcare settings. The results reflect the patient contact with the outdoors and the activities and characteristics the outdoors can and should provide, reflecting a variety of universal needs and opportunities in relation to the outdoor environment in healthcare settings This paper concludes with general quality principles as well as key qualities essential when successful restorative environments around healthcare settings are based on the user‘s actual needs and preferences.